Capacitive behavior of lead free BiNdMnNiO6 double perovskite electronic material. (2021) - Tripathy, A.; Das, S.N.; Bhuyan, S.; Choudhary, R.N.P.
Abstract: An effective and simple method has been developed to synthesize the lead free BiNdMnNiO6 double perovskite material. The synthesis has been carried out through the conventional high-temperature solid-state ceramic processing method. The crystal structure formation has been confirmed with the help of the powder X-ray diffraction method which shows that at room temperature the ceramic exhibits a monoclinic structure. Dielectric and impedance spectroscopy methods have been used to study the significances of frequency and temperature on the conduction mechanism of the ceramic material. The variations of tangent loss and dielectric at different frequencies have been carried out to study the capacitive behavior of the ceramic material. From its impedance study, the existence of a negative temperature coefficient has been affirmed. The important physiochemical properties associated with this compound may be very much essential in the development of next-generation electronic devices.